2016
DOI: 10.1177/0890117116646344
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a National Tobacco Education Campaign on State-Specific Quitline Calls

Abstract: The Tips campaign significantly increased calls to quitlines for almost all the states. These findings underscore the effectiveness of national tobacco media campaigns for reaching state audiences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Among these, promotional efforts, including paid media, have shown increased quitline calls, and paid media is one of the primary methods used by states and the federal government to promote quitlines and increase quitline use. Previous studies have shown a significant relationship between exposure to paid cessation-focused media that directly promotes quitlines or features the quitline telephone number and calls to quitlines [19,20,21,22,23,24]. For this study, we did not estimate the promotional efforts necessary to attain recommended levels of reach, nor did we cost out specific promotional efforts that might be utilized.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, promotional efforts, including paid media, have shown increased quitline calls, and paid media is one of the primary methods used by states and the federal government to promote quitlines and increase quitline use. Previous studies have shown a significant relationship between exposure to paid cessation-focused media that directly promotes quitlines or features the quitline telephone number and calls to quitlines [19,20,21,22,23,24]. For this study, we did not estimate the promotional efforts necessary to attain recommended levels of reach, nor did we cost out specific promotional efforts that might be utilized.…”
Section: Discussionmentioning
confidence: 99%
“…Second, contrary to previous studies 41 , 42 that found that smokers who were ever exposed to the Tips campaign were more likely to exhibit smoking cessation behaviors, our study results suggested that only frequent Tips exposure was positively associated with serious quit attempts. Previous studies 21 , 22 , 23 , 24 , 26 , 43 , 44 that evaluated the effect of the Tips campaign mostly used market-level gross rating points to measure exposure to Tips advertisements. Although gross rating points are less likely to suffer from measurement error and recall bias than self-reported exposure, gross rating points measure area-level aggregated exposure and may not accurately capture the individual-level exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Recent national promotional efforts by the Centers for Disease Control and Prevention (TIPS) directed at smokers, health care providers, and family members have repeatedly demonstrated effectiveness in driving callers to quitline cessation services [73]. The 2016 TIPS campaign featured a woman with a history of depression successful with quitting smoking: https://www.cdc.gov/tobacco/campaign/tips/stories/rebecca.html.…”
Section: Psychosocial Treatment Approaches To Tobacco Use Disordersmentioning
confidence: 99%